The method of plotting a spatial distribution pattern of the total electron content in the region of artificial airglow of the ionosphere - I.A. Nasyrov; D.A. Kogogin; A.V. Shindin; R.V. Zagretdinov; A.B. Beletsky; V.V. Emeljanov (Учёные записки Казанского университета: Серия Физико-математические науки)
The method of plotting a spatial distribution pattern of the total electron content (TEC) in the region of artificial airglow of the ionosphere in the red line of the optical spectrum (λ = 630 nm) was developed during the experiments on disturbances of the ionosphere by powerful radio emission of the SURA facility. To test the method, a measurement session on August 29, 2016 from 18:40 to 20:10 UTC, i.e., when the ionospheric and weather conditions varied slightly and allowed simultaneous optical measurements of the artificial airglow of the ionosphere from two spatially separated sites (Vasilsursk near the SURA facility and Magnitka lying ∼ 170 km East of the SURA facility), was selected. As a result of the simultaneous optical measurements, the area of artificial airglow was plotted in a three-dimensional projection and the spatial position of the disturbed region of the ionosphere stimulated by the powerful radio emission of the SURA facility was determined. The method of plotting a spatial pattern of the electron density distribution in the disturbed region of the ionosphere is based on a joint analysis of variations in the TEC on the radio paths “navigation satellite – ground receiving site” for a number of receiving stations of the global navigation satellite systems located within a radius of ∼ 160 km from the SURA facility. By using this method, the values of electron density variations for different spatial cross-sections of the disturbed region of the ionosphere can be obtained. The joint analysis of the experimental data carried out with the help of the method under consideration showed that in the field of the powerful radio wave a disturbed region with the complex structure formed along the magnetic field lines. Plasma inhomogeneities with an increased electron density occurred at the boundaries of the region with a reduced electron concentration. The difference ∆Ne/Ne at the boundaries of the disturbed region, i.e., between the regions with increased and decreased electron density, might reach 10%. The size of the disturbed region is l⊥ ≈ 45 ÷ 60 km across and l|| ≥ 70 km along the Earth's magnetic field lines.